Competências midiáticas e informacionais de líderes de bairros de Araguaína (TO) na relação com a mídia local e comunidade - Vale, Keliane Morais Silva Santos (2024)
With the digital context and, to some extent, considering all media as public goods, the expression of more voices is expected. This statement aligns with the rationale of this research, which is precisely to know what conditions are necessary for the inclusion of individuals in minority positions in communication, especially in local journalism. Previous studies by the author of this dissertation have already found restrictions on participation in local journalism (Vale; Melo, 2020; Vale; Ramos, 2020). This scenario pointed to media and information literacy (MIL) competencies, which in this work are linked to the principles and dialogues of Media and Information Literacy (MIL). It was assumed that social participation in the local communication environment was not yet a relevant factor, which brought up the central research question: what are the MIL competencies of individuals in minority positions in communication? To delineate the research, leaders from peripheral neighborhoods of Araguaína, Tocantins (TO), were selected to learn about their communication practices and assess their relationships with the local media and community. In this way, the lack of land regularization was highlighted as a catalyst for communication processes, with the low level of MIL competencies being a research hypothesis. As for the specific objectives, there were three: a) to outline the profile of the interviewees regarding media and information literacy; b) to understand the relationship of neighborhood leaders with the local media and community; c) to verify the role of the Consultative Council of Neighborhood Associations of Araguaína (CCABA) in promoting communication practices of neighborhood leaders. The research had a qualitative approach, in which in-depth interviews were used. The initial procedure of the research was the selection of two neighborhoods as the study locus: the Cimba sector, which has a small area whose owners or occupants have never had their land situation resolved with the public entity; and the Alto Bonito sector, which is undergoing a legal process of threat to repossession. The interviews were conducted with the presidents of the two mentioned neighborhoods and also with the president of CCABA. The female leadership in the positions in question reveals issues that have not gone unnoticed, but are not the focus of this study. Media and information literacy competencies were the analysis categories mobilized for the development of this dissertation, whose results showed the importance of some of them for the performance of a community leader, of which we highlight, as an example, the ability to ‘participate in social or political activities through networks or in person, in an informed way’. It was also noted that social engagement prior to neighborhood leadership contributed to the empowerment of the interviewees who most demonstrated MIL competencies. Another observation is that the participation of residents in collective projects promoted the "sense of belonging," essential for the formation of the community, and boosted communication, as seen in the fight for land regularization in the Alto Bonito sector. The results partially refute the initial hypothesis of a low level of MIL competencies, as they reveal particularities in the analyzed cases. Neighborhood presidents demobilize/limit their media and information literacy competencies due to factors such as the need for political articulation with public agents and concern with public exposure. The inferences of this dissertation on the role of CCABA in promoting communication practices of neighborhood leaders indicate that there is no inclination of the institution to promote this type of action, and it is perceived that the political relationship in the management of the council interferes with the recognition of media and information literacy competencies for effective democratic participation, highlighting the need to review the council's role.